Western Ireland ; Dublin and Belfast [videorecording] - Givens, John.; Nisbet, Sandra Lenis; Oregon Public Broadcasting (Seattle, Va. Small World Productions, 1993)
Explore the rugged cliffs, ruined fortresses, ancient stone igloos, traditional pub, remote and story Irishmore in Western Ireland. Features the street musicians, Guinness Brewery, stories of Ireland's past at Kilmainham jail. Ancient illuminated Book of Kells and old Irish village in the capital city and in Belfast.
VHS.
Host/co-writer, Rick Steves ; Editor, John Givens.
Keywords: Ireland -- Description and travel; Ireland -- Antiquities; Ireland -- History